Enhanced methane yield by co-digestion of sewage sludge with micro-algae and catering waste leachate - Siddique, Md. Nurul Islam; Zularisam, A. W. (Water Environment foundation, 2018)
The co-digestion of different wastes is a promising concept to improve methane generation during anaerobic process. However, the anaerobic co-digestion of catering waste leachate with algal biomass and sewage sludge has not been studied to date. This work investigated the methane generation by the anaerobic co digestion of different mixtures of catering waste leachate, micro-algal biomass, and sewage sludge. Co digestion of waste mixture containing equal ratios of three substrates had 39.31% higher methane yield than anaerobic digestion of raw sludge. This was possibly due to a proliferation of methanogens during the co digestion period induced by multi-phase digestion of different wastes with different degrees of digestibility. Therefore, co-digestion of catering waste leachate, micro-algal biomass, and sewage sludge appears to be an efficient technology for energy conversion from waste resources. The scientific application of this co digestion technology with these three substrates may play a role in solving important environmental issues of waste management.